System Usability Scale in Information System Application Development Using Systematic Mapping Study - Rahma Yani; Inaayah Nazhifah; M. Ilham Pradika (Institut Riset dan Publikasi Indonesia (IRPI), 2025)
The System Usability Scale (SUS) is a widely used usability evaluation method due to its simplicity and reliability. However, no study has systematically mapped the application of SUS in information system applications. This research aims to conduct a Systematic Mapping Study (SMS) to analyze the use of SUS in 30 international journals indexed in SpringerLink during the 2021–2025 period, focusing on publication trends, application domains, number and types of respondents, respondent criteria, and SUS score results. After the screening process, 28 relevant articles were identified, of which 14 directly employed SUS. The mapping results indicate that the technology domain dominates the application of SUS, with most respondents being general application users, while publication trends show fluctuations with a peak in 2025. These findings are consistent with the research objective, namely to provide a comprehensive overview of SUS usage patterns. The novelty of this study lies in mapping respondent characteristics and variations in SUS scores within the context of information system applications, which has not been systematically mapped before. The results are expected to serve as both an academic reference and practical guidance for developers and researchers in improving system design based on user experience.